Exploration of Community Empowerment in a Village as the Entrance to a Lake in East Java - Zuana, Muhammad Mujtaba Mitra; Toha, Mohamad; Isbahi, M. Baiqun (Malacca: Journal of Management and Business Development, 2024)
The objective of this study is to investigate community empowerment initiatives aimed at providing support to communities located near a Lake in East Java, with a particular focus on Sidomukti village, which serves as the gateway to the Sarangan Lake (TNK). A case study strategy was employed to gather thorough data, utilising data-gathering approaches such as interviews, observation, and documentation. The employed methodology for data analysis is descriptive qualitative. Data analysis involves the systematic arrangement of data, its categorization into distinct units, its integration, the identification of patterns, the selection of significant elements for further investigation, and the formulation of conclusions. The findings of the study revealed that many empowerment initiatives were implemented in KNP-supporting villages, with a particular focus on villages. Notably, the Mandiri Tourism initiative within the National Community Empowerment Programme (PNPM) garnered a favourable reception from the local community. In addition to this, other local community empowerment programmes have emerged from both local and village government endeavours, as well as from the Sidomukti village community itself. One such initiative involves the establishment of tourism awareness clubs. The Sarangan Lake Tourism Association has led to the establishment of various entities in the accommodation industry, transportation services, restaurants, cafes, and art galleries. Additionally, the village-owned enterprise (BUMDES) STW of Village has empowered the local community in the fields of agriculture and agro-tourism. Furthermore, BUMDES has established strong connections with the wider society. BUMDES is comprised of nine hamlets. The organisation comprises three distinct business divisions, including the Coming Business Unit, the Tourism Unit, and the Savings and Loans Unit.